The Effect of Destination Image, Electronic Word of Mouth and Service Quality on Visiting Decisions and Their Impact on Revisit Interest - Sugeng Riyadi; Adi Nurmahdi (Publikasi Indonesia, 2022)
This study aims to determine the effect of destination image, electronic word of mouth and service quality on visiting decisions and their impact on revisit interest. The object of this research is Dunia Fantasi, Ancol, Jakarta. This research was conducted on 170 respondents using a quantitative descriptive method. Therefore, the data analysis used is statistical analysis in the form of Smart PLS. The results of this study indicate that the destination image variable has a positive and significant effect on visiting decisions, electronic word of mouth has a positive and significant effect on visiting decisions, service quality has a positive and significant effect on visiting decisions, and visiting decisions has a positive and significant effect on revisit interest. Destination image has a positive and significant effect on revisit interest, electronic word of mouth has a positive and insignificant effect on revisit interest, service quality has a positive and significant effect on revisit interest.